ANALISIS PERANCANGAN SI-STOK UNTUK MENGURANGI BULLWHIP EFFECT DALAM INDUSTRI GARMEN - Ifan Setyowinarno; Jeffri Dian Asmoro; Yusuf Amrozi (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2020)
The garment industry has a large contribution to Indonesia's exports. Currently, this industry is facing various challenges, including changes in market demand that are getting faster along with the acceleration of the development of world fashion which does not only rely on the seasons but fashion trends, causing orders for apparel to change rapidly causing the high demand for raw materials from each industrial component to become unstable. stable. The obstacle that is often encountered in the implementation of supply chain management is the lack of coordination, causing distortion of information which results in a bullwhip effect. This research uses the literature study method for data collection and the waterfall method for system design. The final result of this research is a stock information system that is expected to reduce distortion of information and clarify coordination between components in a garment industry so as to reduce the bullwhip effect and stabilize demand for raw materials from each industrial component.